"Ciężki cios dotknął nas...". Reakcje władz i społeczeństwa województwa zielonogórskiego na śmierć Józefa Stalina = "Bad plight came to us...". Reactions of the authorities and the residents of Zielona Góra Voivodeship to the death of Joseph Stalin - Mazur, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article concerns the reactions of the residents of Zielona Góra Voivodeship to the death of Joseph Stalin, which were recorded in the documents of the Provincial Committee of the Polish United Workers` Party (KW PZPR) and the Provincial Office for Public Safety (WUBP).
Keywords: województwo zielonogórskie; stalinizm; Stalin, Iosif Vissarionovič (1878-1953); kolektywizacja; społeczeństwo; stalinism; Zielona Góra Voivodeship; collectivization; society